(untitled) (Fiep Bulletin - online, 2014)
Introduction: Urinary incontinence (UI) is one of the problems that affect multiple people being more common in the elderly. The practice of physical causes intraocular pressure abdminal increase, thus making the depression of the pelvic organs and often cause loss of urine. Evaluate urinary incontinence and quality of life through the questionnaire ICIQ - SF (International Consultation on Incontinence Questionnaire - Short Form), and a questionnaire whose complementary function to verify the impact of life and the kind of activity that provides pathology. Objective: To evaluate the incidence of urinary incontinence during exercise. Methods: The present research it is a study of quantitative trait descriptive, aimed at collecting data for women 18 to 25 years with urinary incontinence by the practice of physical activity among 70 questionnaires. Results: Based on the 70 questionnaires were identified in 25 of them a percentage of 76% with respect to 19 women who practice the high-intensity activities had urinary incontinence, and even with 24% or 6 women had IU practicing low-intensity exercise. Conclusion: In the UI there are several risk factors are more common in older people. It is concluded in this study that 100% of the survey population, about 35,71% of the women who practiced some type of physical activity , already had an episode in his sporting life being more common in more intense activities which cause a greater increase in abdominal pressure.